2011
DOI: 10.1088/2040-8978/13/5/053001
|View full text |Cite
|
Sign up to set email alerts
|

Internal flows and energy circulation in light beams

Abstract: We review optical phenomena associated with the internal energy redistribution which accompany propagation and transformations of monochromatic light fields in homogeneous media. The total energy flow (linear-momentum density, Poynting vector) can be divided into spin part associated with the polarization and orbital part associated with the spatial inhomogeneity. We give general description of the internal flows in the coordinate and momentum (angular spectrum) representations for both nonparaxial and paraxia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
492
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(500 citation statements)
references
References 175 publications
8
492
0
Order By: Relevance
“…In contrast, Belinfante's spin momentum p S is a rather enigmatic quantity [26][27][28][29][30][31][32][33] . On the one hand, the spin momentum provides the physical origin of the spin AM of quantum particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Belinfante's spin momentum p S is a rather enigmatic quantity [26][27][28][29][30][31][32][33] . On the one hand, the spin momentum provides the physical origin of the spin AM of quantum particles.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, what generates the spin AM density s / s z? This known paradox 26,34,35 is resolved by representing the zero transverse momentum as an array of infinitely small loops of circulating spin momentum in the (x,y) plane 26,[30][31][32] , see Fig. 1b.…”
Section: Resultsmentioning
confidence: 99%
“…It is a part of a general class of studies in which particles are observed to undergo circulation while immersed in a static force field with nonzero curl (25,49). In addition, Angelsky et al observed orbital angular momentum transfer in circularly polarized Gaussian beams as a manifestation of the macroscopic "spin energy flow," thus confirming the theory of inhomogeneously polarized paraxial beams (34,50).…”
Section: The Evanescent Wave Technique As a Methods Of Angular Momentumentioning
confidence: 91%
“…This is what is required by the general theory [22,23,26], being associated with a divergence-less nature of the quantities given by Eqs. (20) and (33).…”
Section: Application To Surface Plasmon-polaritonmentioning
confidence: 93%